PENINGKATAN HASIL BELAJAR SISWA SMAS NU PALANGKA RAYA PADA MATERI INTENTION WITH BE GOING TO MELALUI MODEL DISCOVERY LEARNING - NIKMAH WAHYUNI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
The low English learning outcomes of class X IPA SMAS NU Palangka Raya require teachers to innovate. One of them is by applying a more student-centered learning model and can increase student understanding. Therefore the authors chose the Discovery Learning learning model as a solution. This study used the Classroom Action Research (PTK) method which consisted of 2 cycles. Each cycle consists of 4 stages, namely planning, implementation of action, observation and reflection. This research was carried out at SMAS NU Palangka Raya in the odd semester of the 2021/2022 academic year. The subjects of this study were class X IPA students at SMAS NU Palangka Raya in the odd semester of the 2021/2022 academic year. The results of the study showed an increase in learning completeness, which was originally in cycle I by 75% of students who completed it to 91.7% of students who completed it in cycle II. These results indicate that the Discovery learning model can improve student learning outcomes in learning English, especially in Intention with be going to material and can be used as an alternative in learning English. ABSTRAKRendahnya hasil belajar Bahasa Inggris siswa kelas X IPA SMAS NU Palangka Raya menuntut guru untuk berinovasi. Salah satunya dengan menerapkan model pembelajaran yang lebih berpusat pada siswa dan dapat meningkatkan pemahaman siswa. Oleh karena itu penulis memilih model pembelajaran Discovery Learning sebagai solusinya. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang terdiri dari 2 siklus. Setiap siklus terdiri dari 4 tahap, yaitu perencanaan, pelaksanaan tindakan, observasi dan refleksi. Penelitian ini dilaksanakan di SMAS NU Palangka Raya semester ganjil tahun pelajaran 2021/2022. Adapun subyek dari penelitian ini adalah siswa Kelas X IPA SMAS NU Palangka Raya semester ganjil tahun pelajaran 2021/2022. Hasil penelitian diperoleh peningkatan ketuntasan belajar yang semula di siklus I sebesar 75% siswa yang tuntas menjadi 91,7% siswa yang tuntas pada siklus II. Hasil tersebut menunjukkan bahwa dengan model pembelajaran Discovery dapat meningkatkan hasil belajar siswa dalam pembelajaran bahasa Inggris khususnya pada materi Intention with be going to dan dapat digunakan sebagai salah satu alternatif dalam pembelajaran bahasa Inggris.